Modeling and Simuiation Of RPC V-I curve (Using Matlab) - Chowdhury, Sreeraka; Biswas, Sushovan Biswas; Mujumdar, Nayana (International Journal of Computer Sciences and Engineering, 2025)
In this paper, I have developed a electronically simulated circuit models of RPC (Resistive Plate Chamber) detector which is a gas filled device used for detecting radiation. The aim of developing the circuit models was to represent the electronic characteristics of RPC detector through the model whose results closely matches the experimental results. In order to find the circuit model which best represented the detector, the total current flowing through the circuit in each case was calculated. The simulation was primarily done using MATLAB Simulink. The results obtained from this was compared with the experimental data.